The Effectiveness of "Laku Pandai" Agent Implementation on Service Development at Bank Kalteng, Pangkalan Bun Branch (International Journal of Economics and Management Research, 2026)
The Branchless Banking Program for Financial Inclusion, locally known as Laku Pandai, is an initiative by the Financial Services Authority (OJK) aimed at expanding access to banking services for unbanked populations, particularly in remote areas. Given Central Kalimantan’s vast geographical characteristics and limited banking infrastructure, the implementation of Laku Pandai serves as a strategic solution to support financial inclusion. The objectives of this study are: 1) To evaluate the effectiveness of Laku Pandai agent implementation at Bank Kalteng, Pangkalan Bun Branch, and 2) To determine whether customers and agents have derived optimal benefits from the presence of these agents. This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with Laku Pandai agents, customers, and bank officials, supplemented by field observations and documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The results indicate that the implementation of Laku Pandai agents at Bank Kalteng, Pangkalan Bun Branch, has generally been effective in improving access to and the quality of banking services for the community. The presence of agents facilitates financial transactions, saves time and costs, and enhances customer convenience. Nevertheless, the program's effectiveness still faces challenges such as network limitations, technological infrastructure, and agent liquidity constraints. This study concludes that while the Laku Pandai program contributes positively to increasing financial inclusion, it requires operational strengthening and support to ensure better and more optimal implementation.